Pengaruh Inventory Intensity Dan Capital Intensity Ratio Terhadap Manajemen Pajak - Nurafifah Nurafifah; Dirvi Surya Abbas; Saleman Hardi Yahawi (Jurnal Mutiara Ilmu Akuntansi, 2024)
The purpose of this study is to determine the effect of Inventory Intensity and Capital Intensity Ratio on Tax Management in Manufacturing Companies in the Consumer Goods Industry Sector for the period 2018-2021. The population of this study includes all manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The sampling technique used purposive sampling technique. Based on the predetermined criteria obtained 11 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis. The results showed that Inventory Intensity did not affect tax management. Capital Intensity Ratio has a positive effect on tax management. Inventory Intensity and Capital Intensity Ratio together have an effect on Tax Management.